Scribal Practices and Approaches Reflected in the Texts Found in the Judean Desert, Revised Second Edition : Material Culture and Writing Practices in Modern Research - Tov, Emanuel, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This monograph revises the first edition of this book (2004) which is long overdue. Many segments needed revision due in large part to the veritable flood of studies published in the wake of the first edition. In other cases, the author changed his mind in his continued study of the scrolls improved by the new images of the Leon Levy Dead Sea Scrolls Digital Library. Hyperlinks to this library are now added to most references to the scrolls. This book covers many aspects of a handbook for those who study the scrolls, material culture, and edit scroll fragments.